Meningkatkan Keputusan Pembelian Konsumen melalui Tangible, Kehandalan (Reliability) dan Daya Tanggap (Responsiveness) dalam Pelayanan - Ash Shadiq Egim; Liza Zulbahri; Imtihan Imtihan; Riche Fermayani (Jurnal Ecogen, 2023)
The purpose of this research is to find out how consumer purchasing decisions at KFC Veteran Padang City Branch are influenced by physical evidence, reliability and responsiveness. This research is correlational research with a quantitative approach. In this study, data was obtained by filling out questionnaires and interviews. This research used 100 respondents as samples using the Simple Random Sampling technique. This research uses multiple regression analysis to analyze the data and uses SPSS 21 to process the data. The main results are: 1). Tangible variables (X1) have a significant effect on purchasing decisions 2). The reliability variable does not have a significant influence on purchasing decisions, 3). The responsiveness variable does not have a significant effect on purchasing decisions. Based on the simultaneous F test, the variables physical evidence, reliability and responsiveness influence purchasing decisions at KFC Veteran Branch. The results of the R square test can be explained by the independent variable, namely 30% of purchasing decisions and the remaining 70% can be explained by other variables not included in this research model.